DEVELOPMENTALISM IN BRAZIL: THE CURRENT DEBATE - Finello, Mariana (2017)
The aim of this paper is to review the current debate in Brazil among the two main developmental group of authors named as the new developmentalists and the social developmentalists. For both groups, the investment is the main variable to explain growth. However, the key variable to push investment is different for either group. For the new developmentalists, the key variable is the exchange rate. For the second group, it is the domestic mass consumption. The contribution of this paper is to present both agendas of economic policy, their main contribution to the current debate on developmentalism in Brazil and discuss how they can be combine with the macroeconomic short-term economic policy.